Policy and Improving the Quality of Public Services in the Era of Regional Autonomy - Uly Fatana; Rusni Mayang Sari; M Yusuf Wirawan (Journal of Law Justice (JLJ), 2025)
Policy and improving the quality of public services are crucial issues in the context of regional autonomy in Indonesia. In the era of regional autonomy, regional governments have broader authority in managing and providing public services to the community. The aim of this research is to analyze the factors that influence the effectiveness of improving the quality of public services and how efforts are made to improve the quality of public services. The research method used is a normative juridical approach to identify best practices and uses secondary data, namely data obtained from. The research results show that the human resource factor of the apparatus is often considered the most important obstacle in the delivery of public services and efforts to improve the quality of public services can be carried out through revitalization, restructuring and deregulation activities in the field of public services. The implication of these findings is the importance of implementing policies that support active community involvement as well as transparent and accountable management in an effort to increase community satisfaction and trust in public services provided by local governments.